Revenue Risk Analysis of Seaweed Cultivation (Kapphaphycus alvarezii and Eucheuma spinosum) in Bungin Permai Village, Tinanggea District, South Konawe Regency - Muhammad Irlansyah; Surni, Surni; Fahria Nadiryati Sadimantara (International journal of technology and education research, 2024)
This research was motivated by the number of seaweed farmers Kapphaphycus Alvarezii and Eucheuma Spinosum who experienced a decrease in income due to the risks that occur starting from planting, maintenance, to harvest. The purpose of this study was to determine how the amount of risk that occurs during the cultivation of seaweed Kapphaphycus Alvarezii And Eucheuma Spinosum, knowing the income of farmers cultivating seaweed Kapphaphycus Alvarezii And Eucheuma Spinosum. The population in this study were seaweed farmers in Bungin Permai Village who cultivated seaweed totaling 52 people, using simple random sampling techniques where some members of the population were used as research samples. The variables in this study were the productivity and income of corn farming farmers. The analysis used in this study is the coefficient of variation obtained by the results of research showing that the risks that occur in cultivation such as damaged seeds, ice-ice disease, crop failure and accidents. can affect the income of seaweed farmers in Bungin Permai Village, so that the average income of Kapphaphycus Alvarezii seaweed farmers is Rp. 3,864,282 / planting period and Eucheuma Spinosum seaweed farmers Rp. 2,340,921 / planting period. And the risk of income obtained by the type of kapphaphycus alvarezii 0.026 and Eucheuma spinosum 0.030